Synchronization of Time Period for Settlement of Dispute Payment of Compensation for the Procurement of the Pandaan Malang Toll Road - Mazarini Maulidia Aizza Udin; Abdul Rachmad Budiono; Yenny Eta Widyanti (East Asian Journal of Multidisciplinary Research, 2023)
Justice in the field of land as a constitutional mandate is a foundation that must be regulated as contained in the provisions of Article 33 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia which states, "Earth and air and the natural resources contained therein are controlled by the state and be used for the greatest prosperity of the people.”1 In order to achieve justice according to the mandate of the constitution, at least it can be realized through infrastructure development efforts in the national strategic project plan. This is in accordance with one of the priorities on President Joko Widodo's agenda to accelerate and continue infrastructure development. One of the many infrastructures that has become the object of a national strategic project is a network of toll roads or usually called toll roads.